Testing a New Anticoagulation Method for Free Flap Reconstruction of Head and Neck Cancers - Ebrahim Karimi; Seyyed Hadi Samimi Ardestani; Mehrdad Jafari; Ali Bagheri Hagh (Clinical and Experimental Otorhinolaryngology, 2016)
Objectives Free flaps are widely used to reconstruct head and neck defects. Despite the improvement in the surgical techniques and the surgeons’ experiences, flap failures still occur due to thrombotic occlusion after small vessels anastomosis. To reduce the possibility of flap loss as a result of thrombotic occlusion, various anticoagulants have been used. In this study we decided to evaluate a new protocol for anticoagulation therapy and its effect on flap survival and complications. Methods In this interventional study, 30 patients with head and neck cancer underwent surgical defects were reconstructed by microvascular free flap between 2013 and 2014. In the postoperative period patients have taken aspirin (100 mg/day) for 5 days and enoxaparin (40 mg/day subcutaneously) for 3 days. The flap survival was followed for three weeks. Results Given that there was no complete necrosis or loss of flap, the free flap success rate was as much as 100%. The need for re-exploration occurred in 3 patients (10%). Only in one patient the need for re-exploration was due to problem in venous blood flow. Conclusion The aspirin-enoxaparin short-term protocol may be a good choice after free flap transfer in reconstruction of head and neck surgical defects.